NOBCChE News, Volume 18, Number 2 (National Organization for Black Chemists and Chemical Engineers, 1997)
Fall 1997 issue of the NOBCChE News. This is the 25th-anniversary edition of the National Organization for the Professional Advancement of Black Chemists and Chemical Engineers (NOBCChE) Newsletter.
Keywords: National Organization for Black Chemists and Chemical Engineers; Chemists; Chemical engineers; African American chemists; African American engineers; Newsletters; Periodicals; Scientists, Black; African American scientists